Implementasi Prinsip Good Corporate Governance dalam Pengelolaan Dana Desa Bagan Jawa Kecamatan Bangko di Kabupaten Rokan Hilir - Mivtahul Janati Rahmi Fajri; Evi Marlina (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The purpose of this study was to determine whether the management of village funds in Bagan Jawa Village, Bangko District, Rokan Hilir Regency was in accordance with the principles of Good Corporate Governance. The research method used a qualitative descriptive method using two data, namely primary data and secondary data. Primary data was obtained from interviews with informants, documentation in internship activities and observations. Secondary data was obtained from the results of previous research studies related to the research topic. The results of the study showed that the management of village funds in Bagan Jawa Village was in accordance with the principles of Good Corporate Governance. In its implementation, it is still lacking with limited adequate technology and Human Resources who are lacking in managing due to several factors such as lack of other education. Researchers have limited time in research during the internship activities carried out for two months so that it has an impact on the results of the research which are less comprehensive and obtain limited information. Researchers hope that further researchers can conduct comprehensive research by raising broader factors so that the results of the research can be obtained better.